PENGARUH PMTB, INFLASI DAN UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI DAN DISPARITAS PENDAPATAN PROVINSI BALI - Adnyaswari, Anak Agung Mas Ari; Purbhadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023DO - 10.24843/EEB.2023.v12.i11.p07, 2023)
This study aims to (1) analyze the direct effect of GFCF, inflation and minimum wages on economic growth in districts/cities in Bali Province, analyze the direct effect of PMTB, inflation and minimum wages on income disparities in districts/cities in Bali Province, (2) and analyze the influence of GFCF, inflation and minimum wages on income disparities indirectly through the economic growth of districts/cities in Bali Province. This research was conducted in the Province of Bali, with the data source from the Central Bureau of Statistics of the Province of Bali. The analysis technique used is Path analysis using data from 2010 – 2020. The results of data analysis show that (1) GFCF has a positive and significant effect on economic growth, (2) minimum wages have a positive and insignificant effect on economic growth, (3) inflation has a negative and significant effect on economic growth, (4) Inflation and the minimum wage have a negative and significant effect on income disparities, (5) GFCF has a negative and significant effect on disparity, and (6) GFCF, inflation, and the minimum wage have a negative and significant effect to income disparities through economic growth.